Engineering the Single Domain Antibodies Targeting Receptor Binding Motifs Within the Domain III of West Nile Virus Envelope Glycoprotein - Hruškovicová, Jana; Bhide, Katarína; Petroušková, Patrícia; Tkáčová, Zuzana; Mochnáčová, Evelína; Čurlík, Ján; Bhide, Mangesh; Kulkarni, Amod (Frontiers in Microbiology, 2022)
West Nile virus (WNV) is a mosquito-borne neurotrophic flavivirus causing mild febrile illness to severe encephalitis and acute flaccid paralysis with long-term or permanent neurological disorders. Due to the absence of targeted therapy or vaccines, there is a growing need to develop effective anti-WNV therapy. In this study, single-domain antibodies (sdAbs) were developed against the domain III (DIII) of WNV’s envelope glycoprotein to interrupt the interaction between DIII and the human brain microvascular endothelial cells (hBMEC). The peripheral blood mononuclear cells of the llama immunized with recombinant DIIIL297–S403 (rDIII) were used to generate a variable heavy chain only (VHH)-Escherichia coli library, and phage display was performed using the M13K07ΔpIII Hyperphages system. Phages displaying sdAbs against rDIII were panned with the synthetic analogs of the DIII receptor binding motifs, DIII-1G299–K307 and DIII-2V371–R388, and the VHH gene from the eluted phages was subcloned into E. coli SHuffle. Soluble sdAbs purified from 96 E. coli SHuffle clones were screened to identify 20 candidates strongly binding to the synthetic analogs of DIII-1G299–K307 and DIII-2V371–R388 on a dot blot assay. Among them, sdAbA1, sdAbA6, sdAbA9, and sdAbA10 blocked the interaction between rDIII and human brain microvascular endothelial cells (hBMECs) on Western blot and cell ELISA. However, optimum stability during the overexpression was noticed only for sdAbA10 and it also neutralized the WNV–like particles (WNV-VLP) in the Luciferase assay with an half maximal effective concentration (EC50) of 1.48 nm. Furthermore, the hemocompatibility and cytotoxicity of sdAbA10 were assessed by a hemolytic assay and XTT-based hBMEC proliferation assay resulting in 0.1% of hemolytic activity and 82% hBMEC viability, respectively. Therefore, the sdAbA10 targeting DIII-2V371–R388 of the WNV envelope glycoprotein is observed to be suitable for in vivo trials as a specific therapy for WNV–induced neuropathogenesis.